Copper-resistant microorganisms isolated from Antarctic island Galindez - Matveeva, N. A.; Tashyreva, G. O.; Tashyrev, O. B. (Ukrainian Antarctic Journal, 2006)
The copper-resistant microorganisms were isolated from soils of Antarctic island Galindes. It was shown that these microorganisms can grow on the medium with concentration of Cu2+ ions 1000–3000 ppm.